PENERAPAN ASAS PERADILAN CEPAT, SEDERHANA, DAN BIAYA RINGAN DALAM PRAKTEK PERSIDANGAN ISBAT NIKAH MASSAL DI PENGADILAN AGAMA KELAS IA MAKASSAR TAHUN 2020 - Muh Rafli Faturrahman; Muh. Jamal Jamil; Rahma Amir (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2025)
This study discusses the Application of the Principles of Fast, Simple, and Low-Cost Trials in the Practice of Mass Marriage Isbat Trials at the Makassar IA Religious Court in 2020. The main issues consist of two sub-problems: the practice of Mass Marriage Isbat trials at the Makassar Class IA Religious Court and the implementation of The principle of fast, simple, and low-cost tests at the Makassar Class IA Religious Court. This study uses empirical legal research, which is a type of legal research method that is carried out by examining the actual situation that occurs in society. This research uses a sociological approach, a normative approach (sari), and a juridical approach. The data collection methods used are interviews, observation, and documentation. The results of this study indicate that applying the principle of expeditious justice in trials of mass marriages at the Class 1A Makassar Religious Court in 2020 has provided benefits in speeding up the trial process. With a more efficient and fast operation, the parties involved in the trial can immediately obtain a final decision. The principle of simple justice has been proven to provide easy access for the public to submit requests for constituencies for mass marriages. The simple and uncomplicated procedure makes it easier for the public to understand the processes and requirements that must be met, thereby providing more expansive opportunities for those who wish to enter into a marriage bond. Keywords: Principles of Justice, Marriage Isbat, Trials.